2017
DOI: 10.1088/1741-4326/aa4ff8
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of energy transport in DIII-D High-βPEAST-demonstration discharges with the TGLF turbulent and NEO neoclassical transport models

Abstract: Energy transport analyses of the DIII-D high- EAST-demonstration discharges have been performed using the TGYRO transport package with the TGLF turbulent and NEO neoclassical transport models under the OMFIT integrated modeling framework. Ion energy transport is shown to be dominated by neoclassical transport and ion temperature profiles predicted by TGYRO agree closely with the experimental measured profiles for these high- discharges. Ion energy transport is largely insensitive to reductions in the flow she… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
58
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(65 citation statements)
references
References 47 publications
7
58
0
Order By: Relevance
“…In the electromagnetic simulations it is found that ion scale turbulence suppresses electron scale fluctuations due to zonal flow mixing. A new saturation model in TGLF that incorporated this effect improved accuracy of temperature predictions, with the electromagnetic effects reducing temperature gradients, to achieve a better match to experiment as shown in Fig. 24 [74]. These effects, and discrepancies with experiment become more pronounced at higher q 95 ; there is clearly much further work to do to resolve transport models for high b advanced tokamak plasma configurations.…”
Section: Effect Of High Bmentioning
confidence: 95%
See 1 more Smart Citation
“…In the electromagnetic simulations it is found that ion scale turbulence suppresses electron scale fluctuations due to zonal flow mixing. A new saturation model in TGLF that incorporated this effect improved accuracy of temperature predictions, with the electromagnetic effects reducing temperature gradients, to achieve a better match to experiment as shown in Fig. 24 [74]. These effects, and discrepancies with experiment become more pronounced at higher q 95 ; there is clearly much further work to do to resolve transport models for high b advanced tokamak plasma configurations.…”
Section: Effect Of High Bmentioning
confidence: 95%
“…Experimental and modeling investigations performed in the last few years by an international joint team of scientists working on DIII-D and EAST have made great progress toward developing the high poloidal beta (eb P C 1) regime as a basis for the steady state operation of a tokamak fusion reactor [37,[69][70][71][72][73][74][75]. Plasma operation in the high poloidal beta regime ameliorates two key weakness of the tokamak configuration: current disruptions and the need for external current drive.…”
Section: High B P Scenariomentioning
confidence: 99%
“…This suggests that the that the large radius ITB and the pedestal could be coupled. However, a high pedestal state with large fluctuations in β N due to n = 1 ELMs has previously been observed with an ITB and high confinement [13] in this scenario suggesting that the ITB does not prohibit the high pedestal. To understand what role the Shafranov shift plays in sustainment of the ITB, we examine how α − s changes versus ρ, which is shown in Figure 3.…”
mentioning
confidence: 62%
“…Note that a peak of the density fluctuation spectra near 100-130 kHz (blue curve in figure 2(c)) is the TAE activity, not the turbulence. Transport analysis for an example of discharge 154 372 suggests that the E × B shear effect is not key to the ITB formation in DIII-D high β P discharges [14]. In the analysis, the electron temperature, electron density and toroidal rotation profiles are fixed and only the ion temperature profile is predicted by TGYRO [6] with TGLF [7] for turbulent transport, and NEO [8] for neoclassical transport, to investigate the ion channel energy transport.…”
Section: Extension Of High Bootstrap Fraction Scenarios Toward Low Pl...mentioning
confidence: 99%